Intermittent Capture of the Left Bundle With Permanent His Bundle Pacing: Mechanistic Insights and Implications for an Emerging Field. (29th August 2016) - FRIEDMAN, DANIEL J.; HJORTH, MARKUS A.; SUN, ALBERT Y.; ATWATER, BRETT D.
LBBB and His Bundle Pacing: We present a case of a patient with elevated His lead capture thresholds and intermittent recruitment of the left bundle. The patient underwent a noninvasive electrophysiology study and was determined to have a left bundle branch block due to postrepolarization refractoriness. The nature of bundle branch block can have important implications for optimal patient selection and device programming in the emerging field of His bundle pacing.